P-Wave and QT Dispersions on Electrocardiography in Coronary Artery Slow Flow Phenomenon - Yılmaz, Mücahid; Korkmaz, Hasan; Uku, Ökkeş; Kurtoğlu, Ertuğrul; Bilen, Mehmet Nail; Akbulut, Mehmet (My University, 2017)
Introduction: The purpose of this study was to analyse P-wave and QT dispersions on electrocardiographyin patients with CSFP and compare the findings with those of patients with NCA.Patients and Methods: This study included a total of 82 patients (40 patients with NCA and 42 patients with CSFP). Coronary blood flow was calculated according to the thrombolysis in myocardial infarction (TIMI) frame count. Electrocardiograms were obtained at a rate of 50 mm/s and amplitude of 20 mV, including at least 3 QRS complexes for each derivation, and were taken with 12 standard deviations. The longest P-wave duration was defined as Pmax, and the shortest P-wave duration was defined as Pmin. The difference between Pmax and Pmin was defined as P-wave dispersion. QTc, which is the QT interval corrected for heart rate, was measured according to Bazett’s formula. The difference between the longest QTc and shortest QTc was considered as QTc dispersion. All measurements were performed manually.Results: This study demonstrated that P-wave dispersion (53.2 ± 5.35 and 46.07 ± 4.12, p < 0.0001, respectively), Pmax (106.2 ± 10.11 and 97.7 ± 8.17, p< 0.0001, respectively), maximum QTc (438.96 ± 16.77and 426.13 ± 10.01, p< 0.0001, respectively) and QTc dispersion (68.99 ± 4.34 and 61.64 ± 4.15, p< 0.0001, respectively) were significantly prolonged in the CSFP group than the NCA group.Conclusion: This study demonstrated that P-wave and QTc dispersions were prolonged in the CSFP group.
Keywords: Kalp ve Kalp Damar Sistemi